Exploring Contemporary Counterterrorism and Perspectives of Terrorism Experts to Combat Boko Haram - Njoku, Enyinaya (2020)
Within the last decade, the terrorist attacks by Boko Haram have been the topic of considerable scholarly focus; yet, there remains a lack of knowledge and understanding about the causes of failure in counterterrorism measures by the Nigerian government in Borno State. Using Wilner’s contemporary deterrence theory as the foundation, the purpose of this case study of the Nigeria Police Force (NPF) was to bridge the gap in knowledge to understand the causes of failure in counterterrorism measures by the Nigerian government and to explore alternate approaches to the counterterrorism efforts in Borno State to deter Boko Haram. Data were collected through interviews with 10 NPF counterterrorism experts selected through a purposive sampling strategy. These data were inductively coded and analyzed using Braun and Clarke’s thematic analysis procedure. Two primary themes emerged from this study: (a) counterterrorism measures used by the Nigerian government were ineffective and (b) the important distinctions in the perceptions of the participants. De-radicalization and reorientation measures hold the potent dynamics of an enduring and long-term approach to successful counterterrorism and combating insurgency. The results of this study have implications for positive social change including policy recommendations to the Nigerian government to invest in counterterrorism efforts rooted in trust-building at higher levels of government to reduce the impact of potential infiltration of Boko Haram in government as well as implementing education and outreach programs highlighting the ills of terrorism, making it less attractive for vulnerable youths, enthroning peace and normalcy in the community, and promoting a society devoid of the destructive tendencies of terrorism